Y2Co17-nitrogen-doped graphite carbon nano composite electromagnetic wave absorbing material and preparation method thereof
By coating the surface of Y2Co17 nanoparticles with ultrathin graphite carbon nanolayers, Y2Co17@NGC nanocomposites were prepared, which solved the problem of easy oxidation of rare earth-based metal materials, and achieved high stability and excellent electromagnetic wave absorption performance.
Patent Information
- Application Number
- CN202411745880.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-12-02
AI Technical Summary
Nanostructured rare earth-based metal materials are prone to oxidation, resulting in changes in composition and poor structural stability, limiting their application in high-tech fields.
The Y2Co17@NGC nanocomposite was prepared by co-precipitation method, DA self-polymerization coating and controllable heat treatment. The Y2Co17 nanoparticles were encapsulated through ultra-thin graphite carbon nanoclad layer to enhance their oxygen resistance and structural stability.
It significantly improves the oxygen resistance and structural stability of the Y2Co17 phase, maintains the high purity of rare earth alloys, has good intrinsic magnetic properties and excellent electromagnetic wave absorption performance, and is suitable for electronic communications, aerospace and other fields.
Smart Images

Figure CN119603949A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of rare earth-based metal functional materials and their preparation, and particularly relates to a high-stability Y 2 Co 17 @NGC nanocomposite soft magnetic materials and their preparation methods. Background Art
[0002] High-performance rare earth-based metal materials based on rare earth-metal alloys or compounds are one of the core materials in modern high-tech fields such as electronic and electrical engineering, mechanical manufacturing, and aerospace. The exploration and development of new rare earth-based metal materials has always been an important research topic in the field of materials science and engineering. In recent years, nanostructured rare earth-metal alloys or compounds prepared by various advanced nanotechnologies have outstanding advantages such as diversified material structures and superior physical and chemical properties that are completely different from conventional rare earth-based metal materials. They have broad application prospects in cutting-edge technology fields such as nanocatalysis, low-carbon energy, artificial intelligence, and new generation electronic communications.
[0003] Rare earth metals generally have active chemical properties, which makes them show strong oxidizability in various application environments such as air, moisture, acid, alkali and high temperature compared with other metals. Nanostructured rare earth-based metal materials are more easily oxidized than conventional rare earth-based metal materials due to their large specific surface area and high surface energy. In the process of preparation and application, they face bottleneck problems such as composition changes caused by easy oxidation and poor structural stability. In addition, nanostructured rare earth-based metal materials also face technical problems that need to be solved, such as easy decomposition, difficulty in alloying and difficulty in forming a single alloy phase. Studies have shown that the use of appropriate material composite methods (antioxidant layer coated on the surface of nanoparticles and multiphase composites, etc.) can improve the oxidation resistance and structural stability of nano rare earth-metal alloys or compounds to a certain extent, but it will also bring about obvious changes in the composition and structure of rare earth-based metal materials, thereby affecting their intrinsic physical and chemical properties and reducing their actual material properties. Therefore, it is necessary to develop new preparation methods to enhance the oxidation resistance and structural stability of rare earth-based metal nanomaterials, obtain high-purity and high-stability nanostructured rare earth-based metal alloys or compounds, maintain their intrinsic physical and chemical properties, and meet the requirements of practical applications.
[0004] The present invention provides a high stability Y 2 Co 17 @NGC nanocomposite electromagnetic wave absorbing material and its preparation method. The coprecipitation method, DA self-polymerization coating and controlled heat treatment are used to prepare the material. First, DA and GO are used as carbon sources to completely coat C (graphite carbon) in the phase composition of CoO, Co and Y. 2 O 3 CoO-Co-Y 2 O3 / C core-shell structure composite precursor, and then the above precursors were co-reduced by controlled calcium reduction method to prepare a series of Y with adjustable electromagnetic wave absorption performance 2 Co 17 @NGC nanocomposite electromagnetic absorption material. This ultra-thin graphite carbon nano-coating layer encapsulates Y 2 Co 17 Nanoparticles greatly improve Y 2 Co 17 phase oxidation resistance and structural stability, and maintain the Y 2 Co 17 The high purity of the rare earth alloy in the NGC nanocomposite material gives it good intrinsic magnetic properties and excellent electromagnetic wave absorption performance. By adjusting the ratio of DA and GO, the carbon defects in the NGC modified layer can be changed, thereby adjusting the Y 2 Co 17 @NGC Electromagnetic wave absorption performance of nanocomposite materials. The present invention effectively solves the bottleneck problems such as poor oxidation resistance and structural stability that limit the research and application of nanostructured rare earth alloys, and helps promote the practical application of high-performance rare earth-based metal nanomaterials; it also provides a new surface modification technology for easily oxidized metal nanomaterials, and also provides new ideas for the research and development and application of new metal-based nanomaterials. Summary of the invention
[0005] The object of the present invention is to provide a high stability Y 2 Co 17 @NGC nanocomposite soft magnetic material and its preparation method, the material composition and structural characteristics are: 2 Co 17 The average particle size of the NGC nanocomposite particles is 100-450nm; the NGC surface modification layer with a thickness of 1-4nm is completely and evenly coated on the high-purity Y 2 Co 17 On the surface of nanoparticles, Y 2 Co 17 The oxidation resistance and structural stability of the phase can be improved by adjusting the ratio of DA and GO in the precursor to obtain a DGC surface modification layer with more carbon defects, thereby obtaining Y 2 Co 17 @DGC nanocomposite particles. Its material performance characteristics are: 2 Co 17 @NGC nanocomposites have high saturation magnetization (M s =112.1~113.3emu / g) and higher coercivity ( i H c =242.9~294.6Oe); Y2 Co 17 @NGC nanocomposite soft magnetic material has a maximum absorption intensity range of -69.69 to -80.16 dB in the range of 2 to 18 GHz, and the corresponding absorption frequency range of electromagnetic waves is 4.30 to 7.49 GHz, which is suitable for preparing absorbers for electromagnetic wave absorption in the C-band frequency range; 2 Co 17 @DGC nanocomposite soft magnetic material has a maximum absorption intensity of -20.19 to -68.67 dB in the range of 2 to 18 GHz, and the corresponding frequency range of electromagnetic wave absorption is 13.40 to 16.71 GHz. It is suitable for preparing absorbers for electromagnetic wave absorption in the Ku-band frequency range. As a type of high-performance electromagnetic wave absorption material, it has broad application prospects in fields such as electronic communications and aerospace.
[0006] In order to achieve the above object, the implementation of the technical solution of the present invention includes the following steps:
[0007] (1) Preparation of Y 2 O 3 -Co 3 O 4 Composite oxide@GO composite precursor: an appropriate amount of GO is dissolved in deionized water and ultrasonic dispersion is used to prepare a 0-2 mg / mL GO aqueous solution; commercially available yttrium chloride hexahydrate and cobalt chloride hexahydrate with a molar ratio of 2:14-2:19 are dissolved in 10-30 mL of the above-prepared GO aqueous solution and stirred for 5-30 minutes; then a mixed alkali solution of 0.2-0.4 mol / L sodium hydroxide and 0.1-0.3 mol / L sodium carbonate is quickly poured into the above mixed solution containing yttrium ions, cobalt ions and GO, and its pH value is adjusted to 9-11, and stirring is continued for 10-30 minutes to allow the two metal ions to fully precipitate to obtain a flocculent precipitate. The precipitate was collected by centrifugal separation and washed with deionized water for 6 to 11 times, and then dried in an oven at 30 to 80°C. After grinding, amorphous Y-Co hydroxide @ GO composite powder was obtained. The powder was further placed in a muffle furnace and calcined in air for 2 to 5 hours at a calcination temperature of 300 to 600°C. After cooling in the furnace, Y 2 O 3 -Co 3 O 4 Composite oxide@GO composite precursor.
[0008] (2) Preparation of CoO-Co-Y 2 O 3 / C composite precursor: 0.3-0.8 g of Y prepared in step (1) 2 O 3 -Co 3 O4 The @GO composite precursor was dissolved in 50-200 ml of commercially available Tris-HCl buffer (1.0 M, pH = 8.5), and then 10-100 mg of dopamine hydrochloride was added after ultrasonic dispersion for 0.5-2 hours. The magnetic stirring was continued for 12-24 hours, and then the composite particles coated with PDA on the surface were collected by centrifugation. The PDA-coated particles were washed 3-5 times with deionized water and anhydrous ethanol and then dried in a vacuum drying oven at 30-80°C. The dried powder was annealed in an argon atmosphere for 1-4 hours at a temperature of 600-800°C and a heating rate of 2°C / min-5°C / min. After cooling in the furnace, CoO-Co-Y 2 O 3 / C composite precursor.
[0009] (3) Preparation of Y 2 Co 17 @NGC nanocomposite soft magnetic material: The CoO-Co-Y 2 O 3 The Y / C composite precursor, commercially available high-purity calcium particles and analytically pure potassium chloride are uniformly mixed in a mass ratio of 1:1:5 to 1:3:1 and placed in a crucible, and then moved to a controlled atmosphere heat treatment furnace, and in a protective atmosphere of high-purity argon, the temperature is raised from room temperature to 850 to 1000°C at a rate of 2°C / min to 8°C / min, and then cooled in the furnace for 1 to 3 hours to obtain a reaction product; the calcium oxide and unreacted calcium particles in the reaction product are washed with deionized water, and then washed with anhydrous ethanol for multiple times to remove excess water, and then placed in a vacuum drying oven at 30 to 80°C for 3 to 12 hours to obtain Y 2 Co 17 @NGC nanocomposite soft magnetic particles.
[0010] The invention has the advantages of simple preparation process, low production cost and wide applicability. BRIEF DESCRIPTION OF THE DRAWINGS
[0011] Figure 1 Y in Example 1 2 Co 17 X-ray diffraction (XRD) spectra of / DGC nanocomposites
[0012] Figure 2 Y in Example 1 2 Co 17 Scanning electron microscope (SEM) and transmission electron microscope (TEM) morphology of / DGC nanocomposites, where:
[0013] Figure 2 (a) is Y 2 Co 17 SEM morphology of / DGC nanocomposite;
[0014] Figure 2 (b) is Y 2 Co 17 TEM morphology of / DGC nanocomposites;
[0015] Figure 2 (c) is Y 2 Co 17 HRTEM high-resolution image of / DGC nanocomposite;
[0016] Figure 3 Y in Example 1 2 Co 17 X-ray photoelectron spectroscopy (XPS) spectra of Co element in the / DGC nanocomposite and the sample after 2nm surface etching
[0017] Figure 4 Y in Example 1 2 Co 17 / DGC and Y in Example 2 2 Co 17 Raman spectrum of NGC nanocomposite
[0018] Figure 5 Y in Example 1 2 Co 17 Magnetic hysteresis loop of / DGC nanocomposite at the maximum applied magnetic field of 20kOe
[0019] Figure 6 Y in Example 1 2 Co 17 Reflection loss curve of / DGC nanocomposite
[0020] Figure 7 Y in Example 1 2 Co 17 Thermogravimetric (TG) curves of the MgO / DGC nanocomposites from room temperature to 800 °C
[0021] Embodiment 1
[0022] Y with Ku-band frequency range electromagnetic wave absorption 2 Co 17 @DGC nanocomposite materials, among which Y 2 Co 17 The average particle size is 199.2nm, the DGC thickness is about 2.8nm, and the preparation steps are as follows:
[0023] (1) Dissolve 24.84 mg GO in 18 mL deionized water and use ultrasonic dispersion to prepare a 1.38 mg / mL GO aqueous solution; dissolve commercially available yttrium chloride hexahydrate and cobalt chloride hexahydrate in a molar ratio of 2:16.5 in 18 mL of the above-prepared GO aqueous solution and stir for 20 minutes; then quickly pour a mixed alkali solution of 0.35 mol / L sodium hydroxide and 0.15 mol / L sodium carbonate into the above-mentioned mixed solution containing yttrium ions, cobalt ions and GO, adjust its pH value to 10, and continue stirring for 20 minutes to allow the two metal ions to fully precipitate to obtain a flocculent precipitate. Collect the above precipitate by centrifugation, wash it with deionized water 9 times, and then dry it in an oven at 60°C. After grinding, obtain amorphous Y-Co hydroxide @ GO composite powder; continue to place the above powder in a muffle furnace and calcine it in air for 3 hours at a calcination temperature of 450°C. After cooling with the furnace, obtain Y 2 O 3 -Co 3 O 4 Composite oxide@GO composite precursor.
[0024] (2) 0.4 g of Y prepared in step (1) 2 O 3 -Co 3 O 4 The @GO composite precursor was poured into 100 ml of commercially available Tris-HCl buffer (1.0 M, pH = 8.5), and then 50 mg of dopamine hydrochloride was added after ultrasonic dispersion for 1 hour. The magnetic stirring was continued for 24 hours and the product was collected by centrifugation. The product was washed 5 times with deionized water and anhydrous ethanol and dried in a vacuum drying oven at 45°C. The dried powder was annealed in an argon atmosphere for 2 hours at a temperature of 700°C and a heating rate of 2°C / min. After cooling in the furnace, CoO-Co-Y 2 O 3 / C composite precursor.
[0025] (3) The CoO-Co-Y 2 O 3 The mixture of a / C composite precursor, commercially available high-purity calcium particles and analytically pure potassium chloride was uniformly mixed in a mass ratio of 1:2:3 and placed in a crucible, and then moved to a controlled atmosphere heat treatment furnace. Under the protective atmosphere of high-purity argon, the temperature was raised from room temperature to 850°C at a rate of 5°C / min, and the reaction product was obtained after cooling with the furnace after 2 hours of reaction. The calcium oxide and unreacted calcium particles in the reaction product were washed with deionized water, and then washed with anhydrous ethanol for multiple times to remove excess water, and then placed in a 45°C vacuum drying oven for 12 hours to obtain Y 2 Co 17 @DGC nanocomposite soft magnetic particles.
[0026] from Figure 1 It can be seen that for CoO-Co-Y 2 O 3 After the controlled calcium reduction of the / C composite precursor, only Y 2 Co 17 The diffraction peaks of the CoO-Co-Y phase are not found in other single substances, alloys and oxides containing Y or Co. 2 O 3 Controlled calcium reduction of composite particles can produce high-purity single-phase Y 2 Co 17 Combined with the structural research data of other materials in the following text, it can also be found that ultra-thin graphite DGC is coated on high-purity Y 2 Co 17 Therefore, no DGC diffraction peak appears in the XRD spectrum of the product.
[0027] Combination Figure 2 (a) SEM, Figure 2 TEM morphology in (b) and Figure 2 As can be seen from the HRTEM high-resolution image in (c), the dense DGC modification layer with a thickness of about 2.8 nm completely covers the nearly spherical Y 2 Co 17 The average particle size of Y particles on the surface of nanoparticles is about 199.2 nm. 2 Co 17 / DGC nanocomposite particles.
[0028] from Figure 3 Middle Y 2 Co 17 The Co element XPS spectra of the / DGC nanocomposite and the samples after 2nm surface etching show that 2 Co 17 In the / DGC nanocomposites, not only Co 2+ The XPS characteristic peaks of metallic Co were also observed; and the XPS characteristic peak intensity of metallic Co in the sample after 2nm surface etching was significantly higher than that of the unetched sample. The results of XPS research show that Y 2 Co 17 Y / DGC nanocomposites 2 Co 17 The phase has extremely high purity and weak surface oxidation, and its surface oxide layer does not exceed 2nm.
[0029] contrast Figure 4 Middle Y 2 Co 17 / DGC and Y 2 Co 17 From the Raman spectra of carbon in / NGC, it can be found that the Raman spectra of DGC and NGC modified layers both show the characteristics of graphite carbon, and the two also have significantly different carbon defects.
[0030] from Figure 5 It can be seen that due to Y 2 Co 17 @DGC nanocomposite contains ultra-high purity Y 2 Co 17 Nanoparticles and ultrathin DGC modified layer, Y 2 Co 17 / DGC nanocomposite material M s The value is as high as 112.1emu / g; due to Y 2 Co 17 Flower-like microstructure and surface modification of DGC, Y 2 Co 17 @DGC nanocomposites have high i H c value (242.9Oe).
[0031] from Figure 6 It can be seen that Y 2 Co 17 / DGC nanocomposite materials have excellent electromagnetic wave absorption performance: in the range of 2 to 18 GHz, the maximum absorption intensity of electromagnetic waves is -52.59 dB, and the corresponding electromagnetic wave absorption frequency is 16.71 GHz.
[0032] from Figure 7 From the TG curve, we can see that Y 2 Co 17 When the / DGC nanocomposite material is heated from room temperature to 200℃ in air, its weight hardly increases; when it is further heated to 300℃, its weight increases slowly; the results of TG test show that the dense DGC modified layer is completely coated on the high-purity Y 2 Co 17 The surface of the nanoparticles makes Y 2 Co 17 / DGC nanocomposite structure has excellent oxidation resistance and temperature stability.
[0033] Y prepared in this example 2 Co 17 The / DGC nanocomposite material has excellent oxidation resistance and structural stability. In the range of 2 to 18 GHz, the maximum absorption intensity of electromagnetic waves is -52.59 dB, and the corresponding frequency of absorbed electromagnetic waves is 16.71 GHz. It is suitable for preparing absorbers for absorbing electromagnetic waves in the Ku-band frequency range.
[0034] Embodiment 2
[0035] Y with C-band frequency range electromagnetic wave absorption 2 Co 17 @NGC nanocomposite materials, among which Y 2 Co 17 The average particle size is 114.7nm, and the NGC thickness is about 1.5nm. The preparation steps are as follows:
[0036] (1) Dissolve commercially available yttrium chloride hexahydrate and cobalt chloride hexahydrate in a molar ratio of 2:16.5 in 18 mL of deionized water and stir for 20 minutes until fully dissolved; then quickly pour a mixed alkali solution of 0.35 mol / L sodium hydroxide and 0.15 mol / L sodium carbonate into the aqueous solution containing yttrium ions and cobalt ions, adjust its pH value to 10, and continue stirring for 20 minutes to allow the two metal ions to fully precipitate to obtain a flocculent precipitate. Collect the above precipitate by centrifugation and wash it with deionized water 9 times, then dry it in an oven at 60°C, and grind it to obtain an amorphous Y-Co hydroxide composite powder; continue to place the above powder in a muffle furnace and calcine it in air for 3 hours at a calcination temperature of 450°C, and obtain Y after cooling in the furnace. 2 O 3 -Co 3 O 4 Composite oxide composite precursor.
[0037] (2) 0.4 g of Y prepared in step (1) 2 O 3 -Co 3 O 4 The composite precursor was poured into 100 ml of commercially available Tris-HCl buffer (1.0 M, pH = 8.5), and then 50 mg of dopamine hydrochloride was added after ultrasonic dispersion for 1 hour. The magnetic stirring was continued for 24 hours and the product was collected by centrifugation. The product was washed 5 times with deionized water and anhydrous ethanol and then dried in a vacuum drying oven at 45°C. The dried powder was annealed in an argon atmosphere for 2 hours at a temperature of 700°C and a heating rate of 2°C / min. After cooling in the furnace, CoO-Co-Y 2 O 3 / C composite precursor.
[0038] (3) The CoO-Co-Y 2 O 3The mixture of a / C composite precursor, commercially available high-purity calcium particles and analytically pure potassium chloride was uniformly mixed in a mass ratio of 1:2:3 and placed in a crucible, and then moved to a controlled atmosphere heat treatment furnace. Under the protective atmosphere of high-purity argon, the temperature was raised from room temperature to 850°C at a rate of 5°C / min, and the reaction product was obtained after cooling with the furnace after 2 hours of reaction. The calcium oxide and unreacted calcium particles in the reaction product were washed with deionized water, and then washed with anhydrous ethanol for multiple times to remove excess water, and then placed in a 45°C vacuum drying oven for 12 hours to obtain Y 2 Co 17 @DGC nanocomposite soft magnetic particles.
[0039] Y prepared in this example 2 Co 17 / NGC nanocomposite materials have excellent antioxidant properties and structural stability. In the range of 2 to 18 GHz, the maximum absorption intensity of electromagnetic waves is -80.16 dB, and the corresponding frequency of absorbed electromagnetic waves is 4.30 GHz. They are suitable for preparing absorbers for absorbing electromagnetic waves in the C-band frequency range.
[0040] Embodiment 3
[0041] Y with Ku-band frequency range electromagnetic wave absorption 2 Co 17 @DGC nanocomposite materials, among which Y 2 Co 17 The average particle size is 100nm, the DGC thickness is about 1nm, and the preparation steps are as follows:
[0042] (1) Dissolve 15 mg GO in 30 mL deionized water and use ultrasonic dispersion to prepare a 0.5 mg / mL GO aqueous solution; dissolve commercially available yttrium chloride hexahydrate and cobalt chloride hexahydrate in a molar ratio of 2:14 in 30 mL of the above-prepared GO aqueous solution and stir for 30 minutes; then quickly pour a mixed alkali solution of 0.2 mol / L sodium hydroxide and 0.3 mol / L sodium carbonate into the above-mentioned mixed solution containing yttrium ions, cobalt ions and GO, adjust its pH value to 9, and continue stirring for 10 minutes to allow the two metal ions to fully precipitate to obtain a flocculent precipitate. Collect the above precipitate by centrifugation, wash it with deionized water 6 times, and then dry it in an oven at 30°C. After grinding, obtain amorphous Y-Co hydroxide @ GO composite powder; continue to place the above powder in a muffle furnace and calcine it in air for 5 hours at a calcination temperature of 300°C. After cooling with the furnace, obtain Y 2 O 3 -Co 3 O 4 Composite oxide@GO composite precursor.
[0043] (2) 0.3 g of Y prepared in step (1) 2 O3 -Co 3 O 4 The @GO composite precursor was poured into 50 ml of commercially available Tris-HCl buffer (1.0 M, pH = 8.5), and 10 mg of dopamine hydrochloride was added after ultrasonic dispersion for 0.5 hours. The magnetic stirring was continued for 12 hours and the product was collected by centrifugation. The product was washed three times with deionized water and anhydrous ethanol and dried in a vacuum drying oven at 30°C. The dried powder was annealed in an argon atmosphere for 1 hour at a temperature of 600°C and a heating rate of 2°C / min. After cooling in the furnace, CoO-Co-Y 2 O 3 / C composite precursor.
[0044] (3) The CoO-Co-Y 2 O 3 The / C composite precursor, commercially available high-purity calcium particles and analytically pure potassium chloride were uniformly mixed in a mass ratio of 1:1:5 and placed in a crucible, and then moved to a controlled atmosphere heat treatment furnace. Under the protective atmosphere of high-purity argon, the temperature was raised from room temperature to 900°C at a rate of 2°C / min, and the reaction product was obtained after cooling with the furnace after 3 hours of reaction; the calcium oxide and unreacted calcium particles in the reaction product were washed with deionized water, and then washed with anhydrous ethanol for multiple times to remove excess water, and then placed in a 30°C vacuum drying oven for 12 hours to obtain Y 2 Co 17 @DGC nanocomposite soft magnetic particles.
[0045] Y prepared in this example 2 Co 17 The / DGC nanocomposite material has excellent oxidation resistance and structural stability. In the range of 2 to 18 GHz, the maximum absorption intensity of electromagnetic waves is -68.67 dB, and the corresponding frequency of absorbed electromagnetic waves is 13.52 GHz. It is suitable for preparing absorbers for absorbing electromagnetic waves in the Ku-band frequency range.
[0046] Embodiment 4
[0047] Y with Ku-band frequency range electromagnetic wave absorption 2 Co 17 @DGC nanocomposite materials, among which Y 2 Co 17 The average particle size is 450nm, the DGC thickness is about 4nm, and the preparation steps are as follows:
[0048] (1) Dissolve 20 mg GO in 10 mL deionized water and use ultrasonic dispersion to prepare a 2 mg / mL GO aqueous solution; dissolve commercially available yttrium chloride hexahydrate and cobalt chloride hexahydrate in a molar ratio of 2:19 in 10 mL of the above-prepared GO aqueous solution and stir for 5 minutes; then quickly pour a mixed alkali solution of 0.4 mol / L sodium hydroxide and 0.1 mol / L sodium carbonate into the above-mentioned mixed solution containing yttrium ions, cobalt ions and GO, adjust its pH value to 11, and continue stirring for 30 minutes to allow the two metal ions to fully precipitate to obtain a flocculent precipitate. Collect the above precipitate by centrifugation, wash it with deionized water 11 times, and then dry it in an oven at 80°C. After grinding, obtain amorphous Y-Co hydroxide @ GO composite powder; continue to place the above powder in a muffle furnace and calcine it in air for 2 hours at a calcination temperature of 600°C. After cooling with the furnace, obtain Y 2 O 3 -Co 3 O 4 Composite oxide@GO composite precursor.
[0049] (2) 0.8 g of Y prepared in step (1) 2 O 3 -Co 3 O 4 The @GO composite precursor was poured into 200 ml of commercially available Tris-HCl buffer (1.0 M, pH = 8.5), and then 100 mg of dopamine hydrochloride was added after ultrasonic dispersion for 2 hours. The magnetic stirring was continued for 24 hours and the product was collected by centrifugation. The product was washed 5 times with deionized water and anhydrous ethanol and dried in a vacuum drying oven at 80°C. The dried powder was annealed in an argon atmosphere for 4 hours at a temperature of 800°C and a heating rate of 5°C / min. After cooling in the furnace, CoO-Co-Y 2 O 3 / C composite precursor.
[0050] (3) The CoO-Co-Y 2 O 3 The Y / C composite precursor, commercially available high-purity calcium particles and analytically pure potassium chloride were uniformly mixed in a mass ratio of 1:3:1 and placed in a crucible, and then moved to a controlled atmosphere heat treatment furnace. Under the protective atmosphere of high-purity argon, the temperature was raised from room temperature to 1000°C at a rate of 8°C / min, and the reaction product was obtained after cooling with the furnace after 1 hour of reaction. The calcium oxide and unreacted calcium particles in the reaction product were washed with deionized water, and then washed with anhydrous ethanol for multiple times to remove excess water, and then placed in a vacuum drying oven at 80°C for 3 hours to obtain Y 2 Co 17 @DGC nanocomposite soft magnetic particles.
[0051] Y prepared in this example2 Co 17 The / DGC nanocomposite material has excellent oxidation resistance and structural stability. In the range of 2 to 18 GHz, the maximum absorption intensity of electromagnetic waves is -20.19 dB, and the corresponding frequency of absorbed electromagnetic waves is 13.40 GHz. It is suitable for preparing absorbers for absorbing electromagnetic waves in the Ku-band frequency range.
Claims
1. A high-stability Y2Co with tunable electromagnetic wave absorption performance 17 @Nitrogen-doped graphite carbon (NGC) nanocomposite soft magnetic material and its preparation method, the material composition and structural characteristics are: the co-precipitation method, dopamine (DA) self-polymerization coating and controllable heat treatment and other material preparation processes are comprehensively adopted to first completely coat the graphite carbon (C) with DA and graphene oxide (GO) as carbon sources on the surface of composite particles with phase composition of CoO, Co and Y2O3 to form CoO-Co-Y2O3 / C core-shell structure composite precursor, and then the above precursor is co-reduced by controlled calcium reduction method to prepare a series of Y2Co with adjustable electromagnetic wave absorption performance 17 @NGC nanocomposite soft magnetic materials; Y2Co 17 The average particle size of the NGC nanocomposite particles is 100-450nm; the NGC surface modification layer with a thickness of 1-4nm is completely and evenly coated on the high-purity Y2Co 17 On the surface of nanoparticles, Y2Co 17 The oxidation resistance and structural stability of the phase can be improved by adjusting the ratio of DA and GO in the carbon source in the precursor to obtain a NGC surface modification layer (abbreviated as DGC) with more carbon defects, thereby obtaining Y2Co 17 @DGC nanocomposite particles.
2. A high-stability Y2Co with adjustable electromagnetic wave absorption performance according to claim 1 17 @NGC nanocomposite soft magnetic material, its intrinsic magnetic properties are: due to Y2Co 17 @NGC nanocomposites contain ultra-high purity Y2Co 17 Nanoparticles and ultra-thin NGC modification layer, Y2Co 17 @NGC nanocomposite has high saturation magnetization (112.1-113.3emu / g), slightly smaller than Y2Co 17 Corresponding M s Theoretical value of value; due to Y2Co 17 Flower-like microstructure and surface modification of NGC, Y2Co 17 @NGC nanocomposite materials have high coercivity (242.9~294.6Oe).
3. A high stability Y2Co with adjustable electromagnetic wave absorption performance according to claim 1 and claim 2. 17 @NGC nanocomposite soft magnetic material, by adjusting the carbon defects in NGC, it has adjustable electromagnetic wave absorption performance: Y2Co 17 @NGC nanocomposite soft magnetic material has a maximum absorption intensity range of -69.69 to -80.16 dB in the range of 2 to 18 GHz, and the corresponding absorption frequency range of electromagnetic waves is 4.30 to 7.49 GHz, which is suitable for preparing absorbers for electromagnetic wave absorption in the C-band frequency range; Y2Co 17 @DGC nanocomposite soft magnetic material has a maximum absorption intensity of -20.19 to -68.67 dB for electromagnetic waves in the range of 2 to 18 GHz, and the corresponding frequency range of electromagnetic wave absorption is 13.40 to 16.71 GHz. It is suitable for preparing absorbers for electromagnetic wave absorption in the Ku-band frequency range.
4. High stability Y2Co with adjustable electromagnetic wave absorption performance 17 @NGC The preparation method of nano-composite soft magnetic material is characterized in that The following steps are involved: Step 1: prepare an amorphous Y-Co hydroxide @GO composite precursor by a coprecipitation method, grind it into powder after drying, and then continue to calcine in air to obtain a Y2O3-Co3O4 composite oxide @GO composite precursor. Step 2: In an alkaline buffer solution containing dopamine, the self-polymerization reaction of dopamine is used to coat the polymerized dopamine (PDA) on the surface of the Y2O3-Co3O4@GO composite structure to form Y2O3-Co3O4@GO / PDA composite particles, and then a CoO-Co-Y2O3 / C composite precursor is obtained through an appropriate heat treatment process. Step 3: Co-reduction of the CoO-Co-Y2O3 / C composite precursor by controlled calcium reduction to obtain Y2Co 17 @NGC nanocomposite soft magnetic materials.
5. High stability Y2Co with adjustable electromagnetic wave absorption performance 17 @NGC The preparation method of nanocomposite soft magnetic material is characterized by: In claim 3, step 1 is achieved by the following method: dissolving an appropriate amount of GO in deionized water and preparing a 0-2 mg / mL GO aqueous solution by ultrasonic dispersion; dissolving commercially available yttrium chloride hexahydrate and cobalt chloride hexahydrate in a molar ratio of 2:14-2:19 in 10-30 mL of the above-prepared GO aqueous solution, and stirring for 5-30 minutes; then quickly pouring a mixed alkali solution of 0.2-0.4 mol / L sodium hydroxide and 0.1-0.3 mol / L sodium carbonate into the above-mentioned mixed solution containing yttrium ions, cobalt ions and GO, adjusting its pH value to 9-11, and continuing to stir for 10-30 minutes to fully precipitate the two metal ions to obtain a flocculent precipitate. The precipitate is collected by centrifugal separation, washed with deionized water for 6 to 11 times, and then dried in an oven at 30 to 80°C. After grinding, an amorphous Y-Co hydroxide @GO composite powder is obtained. The powder is further placed in a muffle furnace and calcined in air for 2 to 5 hours at a calcination temperature of 300 to 600°C. After cooling in the furnace, a Y2O3-Co3O4 composite oxide @GO composite precursor is obtained.
6. High stability Y2Co with adjustable electromagnetic wave absorption performance 17 @NGC The preparation method of nanocomposite soft magnetic material is characterized by: In claim 3, step 2 is achieved by the following method: pouring 0.3 to 0.8 grams of the Y2O3-Co3O4@GO composite precursor prepared by step 1 into 50 to 200 milliliters of commercially available Tris-HCl buffer (1.0M, pH = 8.5), adding 10 to 100 milligrams of dopamine hydrochloride after ultrasonic dispersion for 0.5 to 2 hours, continuing magnetic stirring for 12 to 24 hours, and then centrifugally collecting the composite particles coated with PDA on the surface; washing the PDA-coated particles with deionized water and anhydrous ethanol for 3 to 5 times and drying them in a vacuum drying oven at 30 to 80°C; annealing the dried powder in an argon atmosphere, the annealing time is 1 to 4 hours, the annealing temperature is 600 to 800°C, the heating rate is 2°C / min to 5°C / min, and the CoO-Co-Y2O3 / C composite precursor is obtained after cooling with the furnace.
7. High stability Y2Co with adjustable electromagnetic wave absorption performance 17 @NGC The preparation method of nanocomposite soft magnetic material is characterized by: In claim 3, step 3 is achieved by the following method: the CoO-Co-Y2O3 / C composite precursor obtained in step 2, commercially available high-purity calcium particles and analytically pure potassium chloride are uniformly mixed in a mass ratio of 1:1:5 to 1:3:1 and placed in a crucible, and moved to a controlled atmosphere heat treatment furnace, and in a protective atmosphere of high-purity argon, the temperature is increased from room temperature to 850 to 1000°C at a rate of 2°C / min to 8°C / min, and the reaction is performed for 1 to 3 hours, followed by cooling with the furnace to obtain a reaction product; the calcium oxide and unreacted calcium particles in the reaction product are washed with deionized water, and then the excess water is removed after washing with anhydrous ethanol for multiple times, and the reaction product is placed in a vacuum drying oven at 30 to 80°C and dried for 3 to 12 hours to obtain Y2Co 17 @NGC nanocomposite soft magnetic particles.
Citation Information
Patent Citations
Preparation method and application of integrated polysaccharide / 3D nitrogen-doped graphene-carbon nanotube composite material
CN110610818A
Gold particle-loaded magnetic nano hollow material as well as preparation method and application thereof
CN110898854A
Two-dimensional CoNi@porous carbon material and preparation method and application thereof
CN112877032A
Samarium iron / graphene nano composite material for absorbing electromagnetic waves and preparation method of samarium iron / graphene nano composite material
CN114682788A
PC / Fe3O4-coated PDA hybrid nano composite wave-absorbing material and preparation method thereof
CN115851227A